Co2P encapsulated in N, O co-doped carbons as bifunctional electrocatalysts for oxygen evolution and reduction reactions. (22nd March 2023) - Xie, Haifang; Zeng, Dahai; Du, Bing; Zhang, Peng; Lin, Huaijun; Li, Qingyang; Lin, Zhidan; Li, Wei; Meng, Yuying
Abstract: Exploring highly-efficient and low-cost non-precious metal electrocatalysts for electrochemical reactions such as oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) is of crucial importance for clean and renewable energy technologies. Herein, we report the synthesis of Co2 P encapsulated in N- and O- co-doped carbons (Co2 P@NOCs), which can serve as excellent noble metal-free bifunctional electrocatalysts for OER and ORR in alkaline media. Especially, the Co2 P@NOC-2 electrocatalyst exhibits a low overpotential of 330 mV to deliver the current density of 10 mA cm −2 for OER in 1.0 M KOH solution, with a small Tafel slope of 97 mV dec −1 . With respect to ORR activity, Co2 P@NOC-2 gives positive onset ( E onset ) and half-wave ( E 1/2 ) potentials of 0.90 and 0.75 V ( vs. RHE) in 0.1 M KOH electrolyte, respectively. Additionally, it presents better methanol tolerance and long-term durability as compared to the commercial Pt/C (20 wt ·%) catalyst. The high electrocatalytic activity and good long-term stability toward OER and ORR can be attributed to the conductive heteroatoms-doped carbon layer, the embedded Co2 P active sites and the synergistic effects between them. The strong synergism can significantly promote the electron transfer during the reaction and enhance the OER and ORR performance. Graphical abstract: Co2 P encapsulated in N, O co-doped carbons (Co2 P@NOCs) were successfully synthesized via pyrolysis of Co-containing polypyrrole (Co@PPY) precursors at high temperature and the subsequent phosphidation procedure. Thanks to the synergistic effect of the conductive heteroatoms-doped carbon layer and the embedded Co2 P active sites, these noble metal-free materials have been proven to show remarkable performance toward both oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) in alkaline media with excellent durability. Image 1 Highlights: Co2 P encapsulated in N- and O- co-doped carbons (Co2 P@NOCs) were synthesized. Co2 P@NOCs can serve as bifunctional electrocatalysts for OER and ORR. Active Co2 P species and conductive carbon layer resulted in synergistic effect. The synergism can promote the electron transfer and enhance catalytic performance.